Improved quality of diabetes control reduces complication costs in Bulgaria. Issue 1 (1st January 2019) - Tachkov, Konstantin; Mitov, Konstantin; Mitkova, Zornitsa; Kamusheva, Maria; Dimitrova, Maria; Petkova, Valentina; Savova, Alexandra; Doneva, Miglena; Tcarukciev, Dimitar; Valov, Vasil; Angelova, Galia; Manova, Manoela; et al.
Abstract: The study investigates the quality of diabetes control and its economic implications in Bulgaria for the years 2012–2016. It is a retrospective study of the national diabetes register. Patients were categorized according to type of diabetes, gender, newly diagnosed cases per year, body-mass index (BMI) and achieved disease control. The relative risks for reducing the diabetes-related complications achieved through a 1% reduction of HbA1c were taken from literature data, and macrocosting was used to calculate the saved cost for diabetes complications. The new cases of type 1 diabetes decreased (10% lower in 2016 than in 2012) but the number of new cases with type 2 diabetes increased (12%). In 2012, the average percentage of glycosylated hemoglobin in the second recording at the end of the year was 7.59% (SD 1.85), whereas the second recording of values for 2016 revealed an average value of 7.3% (SD 1.32). The mean yearly reduction in 2012 was 0.05% (SD 1.1) with a slow increase to 0.07% (SD 0.46) in 2016. The absolute risk reduction for all diabetes-related complications was 20.6. The total prevented costs for all complications in the entire population were 20 million BGN. The results for the period 2012–2016 showed improved control of diabetes. The proportion of patients who achieved control increased over the period, reaching over 40% of the afflicted population. The achieved adequate control led to a reduced risk of developing diabetes-related complications, thereby saving costs of 20 million BGN associated with them, and decreasing the burden on the healthcare system.